Analisis Pengaruh Kadar Air dan Porositas terhadap Kuat Tekan, Kuat Tarik, dan Kuat Geser pada Batupasir Formasi Balikpapan dan Pulau Balang, Kabupaten Kutai Kartanegara - Weggie Atanasius Tonapa; Albertus Juvensius Pontus; Rety Winonazada; Tommy Trides; Ardhan Ismail (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2026)
Compressive strength, tensile strength, and shear strength are the primary parameters used to evaluate the mechanical capacity of rocks to withstand loads, endure tension, and resist shear forces. The physical property variables believed to influence these mechanical properties are moisture content and porosity. Moisture content and porosity represent the percentage of water and the volume of pores or voids within the rock, expressed in percent (%). Therefore, this study aims to analyze the influence of moisture content and porosity on the mechanical strength of rocks, specifically compressive strength, tensile strength, and shear strength expressed through cohesion (c) and the internal friction angle (ϕ) in the sandstones of the Balikpapan and Pulau Balang Formations. This research employed laboratory testing of physical and mechanical properties on intact rock samples obtained from sandstone outcrops, which were subsequently processed using statistical analysis methods, including linear regression, the coefficient of determination (R2), and the correlation coefficient (r). The results indicate that variations in moisture content and porosity have a highly significant influence and are inversely proportional to the mechanical strength values of the rock. Specifically, higher moisture content and porosity lead to a decrease in the mechanical strength parameters (compressive, tensile, and shear strength) of the sandstones in both formations. This is evidenced by the negative linear trends and correlation/R2 values ranging from 0.96 to 1.